2015
DOI: 10.1007/s00436-015-4579-8
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the diagnostic efficiency of the questionnaires screening for schistosomiasis

Abstract: Schistosomiasis is the second widespread tropical disease that affects the health of over 240 million people of 78 countries. Questionnaires have been commonly used to diagnose schistosomiasis, while no meta-analysis of their efficacy had been reported previously. This meta-analysis was conducted to assess their diagnostic accuracy of schistosomiasis. Studies published prior to December 1, 2014, that had used questionnaires as a diagnostic tool were searched in PubMed, Medline, EMBASE, and China National Knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…The first systematic search yielded, after removal of duplicates, 662 systematic reviews for which we screened titles and abstracts. Of the 26 systematic reviews selected for full-text screening, we included 11 systematic reviews which focused on the efficacy of diagnosis and treatment of schistosomiasis ( n = 8) and strongyloidiasis ( n = 3) (Figure 1) [19,44,45,46,47,48,49,50,51,52,53]. The updated systematic search for diagnostic testing accuracy studies for schistosomiasis yielded after de-duplication 1961 citations for the screening of titles and abstracts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first systematic search yielded, after removal of duplicates, 662 systematic reviews for which we screened titles and abstracts. Of the 26 systematic reviews selected for full-text screening, we included 11 systematic reviews which focused on the efficacy of diagnosis and treatment of schistosomiasis ( n = 8) and strongyloidiasis ( n = 3) (Figure 1) [19,44,45,46,47,48,49,50,51,52,53]. The updated systematic search for diagnostic testing accuracy studies for schistosomiasis yielded after de-duplication 1961 citations for the screening of titles and abstracts.…”
Section: Resultsmentioning
confidence: 99%
“…We assessed diagnostic and screening tools for Schistosoma spp. in five included systematic reviews [44,45,46,50,53] and eight individual studies [54,55,56,57,58,59,60,61]. The best performing tests were included in the GRADE summary of finding on diagnostic tools for screening schistosomiasis (Table 4 and Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fen Yang et al, (2015). The study for the validity of the questionnaire showed that; diagnostic odds ratio (DOR) was obtained from Schistosoma haematobium (67.68, 95 % confidence interval (CI)=31.48 to145.54), sensitivity 96%, specificity 86%, AUC was 0.96 (26) .…”
Section: Discussionmentioning
confidence: 99%